Promoting positive states: The effect of early human handling on play and exploratory behaviour in pigs - Zupan, M.; Rehn, T.; De Oliveira, D. [UNESP]; Keeling, L. J. (Elsevier, 2016)
It is known that tactile stimulation (TS) during ontogeny modifies brain plasticity and enhances the motor and cognitive skills. Our hypothesis was that early handling including TS would increase play and exploratory behaviour in commercial pigs under standardized test conditions. Piglets from 13 litters were subjected to three handling treatments from 5 to 35 days of age: all the piglets were handled (H), none of the piglets were handled (NH) or half of the piglets in the litter were handled (50/50). At 42 days of age, the pigs' behaviour was observed in pairs in a novel pen with a 'toy' (tug rope). The main results were that more locomotor play was performed by pigs from litters where all or half of them had been handled, whereas social exploratory behaviour was more pronounced in pigs from litters where half of them had been handled. Although behaviour was affected by the interaction of treatment with sex or with weight category, we propose that the handling procedure does seem to have acted to increase locomotor skills and that handling half of the piglets in the litter may have triggered a series of socio-emotional interactions that were beneficial for the whole group.
Keywords: Keywords pig; positive psychology; social behaviour; stressor; welfare